HUBUNGAN PERTUMBUHAN DENGAN FEKUNDITAS HARPODON NEHEREUS YANG BERASAL DARI PERAIRAN JUATA LAUT KOTA TARAKAN - Muchamad Irfan; Diana Purnamasari; Ulva Sari; Haswin .; Fitri . (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2013)
Fish Nomei (Harpodon nehereus) is one of the icons or characteristic of Tarakan City because this fish is only found area surrounding waters in the Tarakan City. The purpose of this study was to determine the growth of Harpodon nehereus approach of morphometric. Knowing fecundity / number of eggs in a single spawning of Harpodon nehereus in Tarakan. Determine the correlation between morphometric and fecundity of Harpodon nehereus in Tarakan.Reseach using descriptive method. Data collection techniques, using survey research design. Nomei fish sampling techniques using a sampling method, purposive sampling method. Sampling was carried out 4 times over two months, each sampling a total of 120 pieces. Harpodon nehereus sampling carried out during low tide the sea water. Results, the first week got value b = 2.7463 with a correlation value of 0.85 which is allometri negative. The second week got value b = 2.1584 with a correlation value of 0.75 allometri negative. The third week the value of b = 1.1366 allometri negative. Week four earned value b = 2.7385 with a correlation value of 0.84 allometri negative. The results overall TKG IV obtained +374125 375 875 range eggs. At TKG I can not find the eggs because the gonads are still in the form of yarn. At TKG V not found. Results of correlation test between morphometric and fecundity of Harpodon nehereushighest correlation values obtained at the second sampling (second week) of 0.96 with the regression equation y = 36.415 x - 47.508. Besides still in the second week of the correlation between the values obtained with fecundity and weight of 0.82 with the regression equation y = 5.7574 x - 7.1296 .Keywords : Morphometry, fecundity, Harpodon nehereus, Aquatic Juata Tarakan